2019
DOI: 10.1186/s12887-019-1638-9
|View full text |Cite
|
Sign up to set email alerts
|

U-shaped relationship between birth weight and childhood blood pressure in China

Abstract: Background The relationship between birth weight and blood pressure has not been well explored in Chinese children and adolescents. The aim of this study was to investigate the relationship between birth weight and childhood blood pressure in China. Methods A total of 15324 children and adolescents (7919 boys and 7405 girls) aged 7–17 years were stratified into six birth weight groups. Analysis of covariance and binary logistic regression were used to analyse the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
2
19
0
1
Order By: Relevance
“…Indeed, U-shaped relationships in disease epidemiology often represent the influence of different processes occurring at either end of a spectrum, resulting in the disruption of normal biological development and function at both ends. [44][45][46] Therefore, it is likely that the increased prevalence of myopia in the "small" and "medium" groups reflects a different set of genetic or environmental factors that slowed the intrauterine FL growth of these participants and concurrently disrupted the coordination between AL and CR during ocular development. One potential such example could be hypertension in pregnancy: our finding that this condition was more prevalent in the "small" FL group compared with the other trajectory groups in our analysis is consistent with existing research that has demonstrated an association between pregnancy-induced hypertension, especially preeclampsia, and fetal growth restriction, including shorter FL.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, U-shaped relationships in disease epidemiology often represent the influence of different processes occurring at either end of a spectrum, resulting in the disruption of normal biological development and function at both ends. [44][45][46] Therefore, it is likely that the increased prevalence of myopia in the "small" and "medium" groups reflects a different set of genetic or environmental factors that slowed the intrauterine FL growth of these participants and concurrently disrupted the coordination between AL and CR during ocular development. One potential such example could be hypertension in pregnancy: our finding that this condition was more prevalent in the "small" FL group compared with the other trajectory groups in our analysis is consistent with existing research that has demonstrated an association between pregnancy-induced hypertension, especially preeclampsia, and fetal growth restriction, including shorter FL.…”
Section: Discussionmentioning
confidence: 99%
“…An impaired fetal growth, either decrease and increase, is strongly associated with immediate and long-term endothelial dysfunction (Krause et al, 2015;Schneider et al, 2015) and cardiovascular disease (Lai et al, 2019). In this context, several studies have aimed to describe the potential presence of early epigenetic markers of programming in umbilical and placental samples derived from diverse complications in human pregnancy.…”
Section: Epigenetic Mechanisms In Placental Endothelial Dysfunctionmentioning
confidence: 99%
“…Low birth weight, an important indicator of prenatal environment, has been associated with differential risk for neonatal mortality [29,30], neurodevelopment and behavioral problems [31,32], and other diseases [33,34].…”
Section: Birth Weightmentioning
confidence: 99%